LINGUISTIC ONTOLOGY AS MEANS OF MODELING OF A COHERENT TEXT - Aitim, A.; Satybaldiyeva, R. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
In real time, the size of information resources in natural language is growing rapidly. The processing of these resources urgently requires the presence of linguistic databases and knowledge. Processing of information resources in natural language requires the presence of text corpora and thesauri. To create and process them, markup languages and ontological models of subject areas are required. Insufficient use of linguistic and ontological knowledge used in information retrieval and automatic text processing applications leads to various problems: irrelevant search, poor-quality categorization and referencing of documents. The existing markup languages mainly contain concepts of Romano-Germanic and Slavic language groups. These puzzles are considered burning in the field of computational linguistics. For these purposes, it is proposed to create a metalanguage and an ontological model of the grammar of the Kazakh language.